As funções docentes e o perfil institucional de professores das universidades privadas brasileiras: em busca de indicadores de qualidade - Scremin, Greice (2009)
This study based upon teacher s functions indicators available at INEP/MEC database (Instituto Nacional de Estudos e Pesquisas Anísio Teixeira of Ministério da Educação e Cultura) was developed according to research line 1 - Formation, knowledge and professional development - of the Post-Graduation Course in Education of the Universidade Federal de Santa Maria (UFSM) and project Observatório da Educação. The main purpose of this study was to provide an analysis of the institutional/teacher s profile of higher education teachers from private Brazilian universities, in order to establish consistent relationships between this profile analysis with the question of higher education quality proposed by the available educational literature. We agreed that the relevance of relating the expansion/massification of private teaching to the quality of higher education offered by private educational institutions became justifiable the implementation of this work. A quanti-/qualitative approach was chosen for this study, because of the distinction of stages or elements requiring the development and use of different methodological strategies for the data analysis; being then, based on documental analysis assumptions, or statistical procedures. Education quality was not discussed in its specificity; instead, we preferred discussing it on how is given the relationship among existent quality indicators upon the teacher s function perspective from Brazilian private education. By considering that the indicators systems have been one of the worldwide most important and used instruments for assessing the development, performance and the quality of national education systems, we have undertaken this research. It aimed to preserve the actions with positive results and to propose changes, when necessary, in quality evaluation scope of higher educational system. So, the quality indicators of Brazilian higher education can only evaluate the teacher s professional dimension, but not the personalities effectively involved, do not taking in account their subjectivity. These teacher s function indicators were restricted only to the kind of regime of work, level of formation, and gender and they did not take in consideration other constitutive elements of its own definition presented by the INEP. Therefore, indicators presented in its database can provide only a partial contribution about quality evaluation of teaching work. Furthermore, under interpretation of these indicators, we can assume they leave gaps on the understanding about what is and what is not validated in higher education.